Inverse problems in engineering mechanics III International Symposium on Inverse Problems in Engneering Mechanics 2001 (ISIP 2001), Nagano, Japan - Tanaka, M. (Masataka), 1943-; Dulikravich, George S.
Inverse Problems are found in many areas of engineering mechanics and there are many successful applications e.g. in non-destructive testing and characterization of material properties by ultrasonic or X-ray techniques, thermography, etc. Generally speaking, inverse problems are concerned with the determination of the input and the characteristics of a system, given certain aspects of its output. Mathematically, such problems are ill-posed and have to be overcome through development of new computational schemes, regularization techniques, objective functionals, and experimental procedures. Thi.